The prospects of panel style nano-battery technology for EV/HEV - Rahman, Mohammed Ataur; Rashid, Muhammad Mahbubur; Mohiuddin, A. K. M.; Mokhtar, Hannan (IEEE Computer Society, 2016)
CO2 reduction is a fundamental driver for lightweight in automotive. Reducing weight of automobile helps improve energy consumption and reduction of CO2 emission. It is estimated that if the weight of automobile can reduced by 100 kg, it saves approximately 8.5 g of CO2 per 100 km travelling.The introduction of EVs is one of the initiatives for the reduction of CO2 emission. This paper presents the prospects of panel style nano-battery technology for EV/HEV builds with CuO filler epoxy resin (ER) sandwiched by Carbon Fiber (CF) and Lithium (Li) plate. The proposed body panel of EV/HEV would reduce the car weight about 20%, contribute on electrical energy storing and releasing capacity of 1.5 kWh (10% of car total power requirement), and CuO filler ER provides the heat insulation for the car which would save about 10% power consumption of air conditioning system. Aluminum laminated polypropylene film has considered with the propsed body panel to prevent EMC effect to the passenger cabin. It is expected that the proposed panel style nanobattery of EV would save 6.00 kWh battery energy equivalent to 2.81 litre of petrol and prevent 3.081 kg of CO2 emission for every 100 km travelling.